JEJAK DAN KIPRAH ULAMA PINRANG AWAL ABAD XX - Wardiah Hamid (Balai Penelitian dan Pengembangan Agama Makassar, 2019)
This study aims to reveal the traces and progress of Pinrang scholars in the early twentieth century. This research is a qualitative research using data collection techniques for interviews and field observations. Then analyze and reduce data presented in the form of description. The results of this study indicate that the traces of the Pinrang cleric that were built along the Jampue coast to the Langnga coast, are intertwined in scientific absorbing networks to Mandar Land, Salemo, Sengkang to Mangkoso and Mecca Land. networks that are interrelated in kinship nodes. Their work can still be detected up to now with some of the manuscripts that they made as well as the pesantren they founded. Likewise, when the Pinrang Regional Secondary Affairs Office (KUADU) was formed in the 1960s. Some of them belong to the government section under the Ministry of Religion